2022
DOI: 10.1007/s10459-022-10129-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between preadmission variables and academic outcomes for postbaccalaureate students in medical school

Abstract: There is currently little guidance for medical school admissions committees regarding how to weigh postbaccalaureate program grades relative to undergraduate grades. This study was designed to address this issue. Admissions data, preclerkship course performance and United States Medical Licensing Exam (USMLE) Step 1 results were analyzed over three years for University of California, San Diego (UCSD) postbaccalaureate premedical (PBPM) students (n = 25), students who participated in other postbaccalaureate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…There is some evidence that standardized test scores and GPA do not necessarily correlate with progression through medical school. Indeed, students with midrange and lower MCAT scores also proceed successfully through their pre-clinical curriculum and pass their first licensure exams (USMLE and COMLEX; Capers and Way, 2015 ; Girotti et al, 2015 , 2020 ; Agahi et al, 2018 ; Busche et al, 2020 ; Schneid et al, 2022a , b ). A reduced emphasis on MCAT would capture more URiM students; however, the key role of the medical school must be recognized in supporting students with lower scores—a collaborative learning environment, diverse peers, and an experiential curriculum have all been highlighted as critical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that standardized test scores and GPA do not necessarily correlate with progression through medical school. Indeed, students with midrange and lower MCAT scores also proceed successfully through their pre-clinical curriculum and pass their first licensure exams (USMLE and COMLEX; Capers and Way, 2015 ; Girotti et al, 2015 , 2020 ; Agahi et al, 2018 ; Busche et al, 2020 ; Schneid et al, 2022a , b ). A reduced emphasis on MCAT would capture more URiM students; however, the key role of the medical school must be recognized in supporting students with lower scores—a collaborative learning environment, diverse peers, and an experiential curriculum have all been highlighted as critical.…”
Section: Resultsmentioning
confidence: 99%
“…A reduced emphasis on MCAT would capture more URiM students; however, the key role of the medical school must be recognized in supporting students with lower scores—a collaborative learning environment, diverse peers, and an experiential curriculum have all been highlighted as critical. The demonstrated success of diversity-targeted pipeline and postbaccalaureate programs in preparing students for degree completion and success in medical school additionally points to the critical importance of improving study-methods and test-taking skills ( Giordani et al, 2001 ; Grumbach and Chen, 2006 ; Goode and Talbot, 2016 ; Upshur et al, 2018 ; Kadavakollu et al, 2022 ; Schneid et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…Medical school and residency applications include standardised objective measures, such as undergraduate GPA, the Medical College Admission Test (MCAT) or the United Stated Medical Licensing Examination (USMLE), as well as a more holistic review of experiences, extracurriculars and personal attributes. A vast amount of research in the admissions literature has shown a correlation between quantitative academic measures and future success in medical school 2–5 . While admissions committees traditionally have placed greater emphasis on these quantitative academic measures, a holistic review has been shown to confer benefits such as increased diversity of matriculants 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…A vast amount of research in the admissions literature has shown a correlation between quantitative academic measures and future success in medical school. [2][3][4][5] While admissions committees traditionally have placed greater emphasis on these quantitative academic measures, a holistic review has been shown to confer benefits such as increased diversity of matriculants. 6,7 As such, in recent years the Association of American Medical College has encouraged medical schools to use a holistic review, which they define as a "selection process which takes into consideration applicants' experiences, attributes, and academic metrics as well as the value an applicant would contribute to learning, practice, and teaching."…”
Section: Introductionmentioning
confidence: 99%